Technical Guidance for Improving Information from Deterministic and Stochastic Modeling for Sectoral Data of Diskominfo Malang Regency - Kusdarwati, Heni; Pramoedyo, Henny; Amaliana, Luthfatul (Journal of Innovation and Applied Technology, 2023)
Data on the number of people with diabetes mellitus in Kanjuruan Hospital and monthly rainfall in Malang are used as examples for extracting information with inferential statistics. The statistic models used are linear and harmonic regression deterministic models and ARIMA and SARIMA stochastic models. The purpose of community service activities is to provide technical guidance on understanding sectoral time series data analysis for Malang Regency Communication and Information Technology employees. Each participant is given a theoretical module, modeling steps and RStudio script. There is an increase in information from the number of people with diabetes mellitus in Kanjuruan Hospital and the monthly rainfall associated with increasing time becomes related to the value of the data itself at the previous time. Descriptively there is an increase in the understanding value of the ARIMA and SARIMA models between before and after technical guidance.